Web 2.0 use in academic libraries of top ranked Asian universities. Issue 3 (3rd June 2019) - Balaji, B. Preedip; M.S., Vinay; B.G., Shalini; J.S., Mohan Raju
Abstract : Purpose: This paper aims to explore recent trends of how Web 2.0 applications were used in 75 academic libraries in Asia through their library websites. Design/methodology/approach: The Times Higher Education Asia University Rankings 2016 was considered for this study and out of 200 top universities ranked, 75 universities were selected for data collection. Using a multi-method approach, this study evaluated key design elements, library service platforms and website content of each academic library website, examining their site features, Web 2.0 types and applications. The criteria for selecting the websites were first the website was in English and second had Web 2.0 applications integrated into the main website. For the ranking of websites, a library web service index was developed, benchmarking from these groups – resource discovery tools, Web 2.0 applications, e-resources, mobile applications, library guides, digital reference services and digital inclusion – as indicators. Findings: The authors found that over two-thirds of Asian university libraries have deployed one or more Web 2.0 applications, though their popularity and implementation vary greatly. Most widely used Web 2.0 applications are Facebook (61.3 per cent), RSS (53.3 per cent), Twitter (46.7 per cent) and YouTube (37.3 per cent). Instant messaging (5.3 per cent) and podcasting (4 per cent) were least applied. With an average of 44 per cent, the diffusion rate of Web information is moderately high among the majority of the Asian university libraries. Originality/value: Many studies explored Web 2.0 applications from developed countries. However, this study attempts evaluating the use of Web 2.0 applications through content, sites and features of academic libraries in Asia, from developing countries perspective.